Utilization of iPSC-derived human neurons for high-throughput drug-induced peripheral neuropathy screening. (December 2017) - Rana, Payal; Luerman, Gregory; Hess, Dietmar; Rubitski, Elizabeth; Adkins, Karissa; Somps, Christopher
Abstract: As the number of cancer survivors continues to grow, awareness of long-term toxicities and impact on quality of life after chemotherapy treatment in cancer survivors has intensified. Chemotherapy-induced peripheral neuropathy (CIPN) is one of the most common side effects of modern chemotherapy. Animal models are used to study peripheral neuropathy and predict human risk; however, such models are labor-intensive and limited translatability between species has become a major challenge. Moreover, the mechanisms underlying CIPN have not been precisely determined and few human neuronal models to study CIPN exist. Here, we have developed a high-throughput drug-induced neurotoxicity screening model using human iPSC-derived peripheral-like neurons to study the effect of chemotherapy agents on neuronal health and morphology using high content imaging measurements (neurite length and neuronal cell viability). We utilized this model to test various classes of chemotherapeutic agents with known clinical liability to cause peripheral neuropathy such as platinum agents, taxanes, vinca alkaloids, proteasome inhibitors, and anti-angiogenic compounds. The model was sensitive to compounds that cause interference in microtubule dynamics, especially the taxane, epothilone, and vinca alkaloids. Conversely, the model was not sensitive to platinum and anti-angiogenic chemotherapeutics; compounds that are not reported to act directly on neuronal processes. In summary, we believe this model has utility for high-throughput screening and prediction of human risk for CIPN for novel chemotherapeutics. Highlights: Human iPSC-derived neurons predict peripheral neuropathy risk. Specific MOAs for chemotherapy-induced peripheral neuropathy detected. High content imaging configuration is useful for drug candidate screening.